10 How do we engage new health care providers (students and new practitioners) in initiatives to reduce overdiagnosis?. (20th August 2018) - Martiny, Frederik; Treadwell, Julian; Gaver, Anat; McCormack, James
Abstract : Objectives: Knowledge and understanding amongst health care providers is in many ways key to reducing the overdiagnosis problem. However, education about overdiagnosis and its causes is often scarce in health care curricula. At the same time, some of the drivers of 'too much medicine' (guidelines, fear of litigation, unwillingness to deviate from the norm) are ubiquitous in the clinical reality for young practitioners, as well as permeating much of the current healthcare education. Discussion and teaching about overdiagnosis thus risks conflicting with people's preunderstanding of good clinical practice and/or the norm in the clinical setting where they practice. This may leave the impression that understanding the issues of overdiagnosis makes clinical practice more complicated and challenges existing practice. In the face of this challenge, the aim of this workshop is to explore ways to engage students and new practitioners in the prevention of overdiagnosis and reduce as much as possible the cognitive conflict. Our objectives are to identify: ways to engage students and new practitioners in a concept that challenges prior beliefs about good clinical practice barriers for engaging people and how we might overcome these barriers how the concepts of overdiagnosis should be integrated into healthcare curricula, and possibly be integrated into bed side education during clinical rotations If we need a campaign or formal courses about overdiagnosis to change the status quo? Methods: This workshop, will consist of 3–10 min presentations from people with experience in engaging students and other health care providers about the problems of overdiagnosis. Participants will also be encouraged to share their own experiences and share ideas not covered in the presentations. Following presentations, participants will be divided into small working groups. Each group will work on a unique aspects of the ideas that come up during presentations and the following debate. Subsequently each group will be encouraged to present their main conclusions for the other groups. Both presentations and new ideas emerging during the workshop will be noted and shared with the participants following the workshop. Conclusions: At the end of this session we want participants to share their take-home-messages, and have us all be inspired to go home, share their ideas, and the ideas of the group, and engage more people in reducing overdiagnosis. Confirmed speakers: James McCormack, Genevieve Bois, Anat Gaver Potential speakers: John Brodersen